Pengaruh Motivation dan Job Satisfaction terhadap Employee Performance Koperasi Simpan Pinjam Sejahtera Bersama (KSP-SB) di Kota Sukabumi - Bambang Somantri; Anisya Salmah Aga (Cakrawala Repositori IMWI, 2018)
In regard with the Indonesian economy, the cooperative as one of the business entities that have the objective to stabilize the Indonesian economy and as one of the drivers of Indonesia's economic growth, is required to improve the work performance of human resources. In Koperasi Simpan Pinjam Sejahtera Bersama (KSP-SB) branch of Sukabumi, it was found that there was a decrease in employee performance. This study aims to analyze the influence of motivation and job satisfaction on employee performance of Koperasi Simpan Pinjam Sejahtera Bersama (KSP-SB) in Sukabumi. A model was designed where employee performance as dependent variable, motivation and job satisfaction as independent variables. Methods of data analysis using a population sample where the number of samples is less than one hundred people as many as 35 employees. Quality testing instruments techniques include test validity and reliability testing, classical assumptions, and techniques of data analysis using descriptive analysis and correlation, while for hypothesis testing used multiple linear regression analysis, T test , and F test using SPSS program. The result of ttest (partially) shows that motivation do not have a significant impact on employee performance. Job satisfaction partially have a positive and significant impact on employee performance, while simultaneously, motivation and job satisfaction have a positive and significant impact on employee performance